Crystal structure of methyl 3-(1H-naphtho[1,8-de][1,3,2]diazaborinin-2(3H)-yl)benzoate, C18H15BN2O2 - Ma Qiang; Miao Zong-Cheng (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C18H15BN2O2, monolinic, P21/n (no. 14), a = 13.61(2) Å, b = 7.389(11) Å, c = 16.34(2) Å, β = 113.91(2)°, V = 1502(4) Å3, Z = 4, R gt(F) = 0.0544, wR ref(F 2) = 0.1651, T = 273 K.